The Authority of the Fatwa of the Majelis Tarjih and Tajdid on Fajr Time in Ponorogo East Java: Between Scholarly Authority and Organizational Compliance - Abdullah, Fuady; Novi Fitia Maliha; Sari, Ima Frafika (UIN Sunan Kalijaga, 2024)
Fatwas are a significant tool in Islamic jurisprudence, regulating human behaviour and shaping society's knowledge and interpretation. In an organization, fatwas have more binding power. However, in responding to it, each faces other societal structures. This research focuses on implementing a tarjih decision (putusan tarjih) by the Tarjih and Tajdid Council (Majelis Tarjih dan Tajdid - MTT) of Muhammadiyah regarding changes in the Fajr time. Using Max Weber's theory of Social Action, this study investigates how the Council's legal-rational authority impacts compliance among followers. The findings show that organisational structure and acceptance of MTT influence Muhammadiyah members' obedience to the fatwa as an authority according to the criteria of Islamic jurisprudence. This study adds to the scholarly understanding of religious authority in contemporary Islamic organizations by focusing on how fatwa-making and its implementation steps affect community behaviour and religious practice. Furthermore, it emphasizes the significance of contextualizing Islamic law in response to local social dynamics, laying the groundwork for future research on the relationship between religious edicts and societal norms in organisational settings. Fatwa memainkan peran penting dalam yurisprudensi Islam dan merupakan alat untuk mengatur perilaku manusia dan membentuk pemahaman dan interpretasi masyarakat. Dalam konteks organisasi, fatwa memiliki kekuatan yang lebih mengikat. Namun, dalam menanggapinya, setiap individu juga dihadapkan pada struktur lain dalam masyarakat. Penelitian ini berfokus pada implementasi putusan tarjih oleh Majelis Tarjih dan Tajdid (MTT) Muhammadiyah terkait perubahan waktu subuh. Dengan menggunakan teori Max Weber tentang tindakan sosial, penelitian ini menyelidiki bagaimana otoritas legal-rasional MTT berdampak pada kepatuhan para pengikutnya. Temuan penelitian menunjukkan bahwa kepatuhan anggota terhadap fatwa dipengaruhi oleh struktur organisasi dan penerimaan terhadap MTT sebagai otoritas menurut kriteria yurisprudensi Islam. Studi ini menambah pemahaman ilmiah tentang otoritas keagamaan dalam organisasi Islam kontemporer dengan berfokus pada bagaimana pembuatan fatwa dan langkah implementasinya mempengaruhi perilaku masyarakat dan praktik keagamaan. Selain itu, studi ini menekankan pentingnya kontekstualisasi hukum Islam sebagai respons terhadap dinamika sosial setempat, yang menjadi dasar bagi penelitian di masa depan tentang hubungan antara fatwa agama dan norma-norma masyarakat dalam konteks organisasi.